Carnavalização do sao joao uma analise do modelo de negocio na festa em senhor do bomfin - Oliveira, Gleise cristiane ferreira de (2009)
The festivities are time to extravagate, to break free from the routine and from the daily rules. However, behind that transgressive character that permeates them, there is a complex organizational logic to which they are submitted. It could not be any different in the case of Senhor do Bonfim’s São João. This monograph has as its purpose to investigate how the festivities of São João in that city is organized and managed, with special attention to the economic aspects and mainly to an eventual process of carnivalization suffered by the traditional festivities of the month of June. In order to perceive the peculiarities of these festivities it is made hereby a comprehensive analysis of them, by confronting them with the ones that characterize the business model of Bahia’s Carnival. The results reveal that, in the same city, two different ways of celebrating coexist. What is hereby called carnivalization certainly occurs in connection with these festivities’ private circuit, which happens to be an alternative to the richer people that desire to partake in a pre-molded and deterritorialized festivity, with some characteristics that are associated to the Carnival of Salvador. On the other hand, this research also reveals that São João’s traditional face is directly linked to another festivity, which takes place in Caruaru-PE, at the same period of the year. Finally, it can be noticed that, in spite of the cultural transformation of São João in Senhor do Bonfim, there is still room for some traditions that have been resisting through the years: the parties in the neighborhood, the folkloric shows, the parties in the city squares and the home-to-home celebrations.